UJI AKTIVITAS REPELLENT FRAKSI KLOROFORM EKSTRAK ETANOL DAUN MIMBA (Azadirachta indica A.Juss) TERHADAP NYAMUK Aedes aegypti - sri susilowati; Fransiska Vita Kurniawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACT Dengue haemorragic fever is a disease caused by dengue virus by mediator Aedes aegypti. The effort of overcoming this disease could be done by preventing the mosquito from bitting using repellent. One of natural repellents is neem (Azadiracta indica A.Juss). This study aimed to determine the repellent activity of chloroform fraction of ethanolic extract neem leaf against Aedes aegypti mosquito. Extraction neem leaf done using ethanol 96% by maceration methode and followed fractionation with chloroform. This study was conducted in 5 groups, positive control (DEET 13%), negative control (liquid paraffin) and three series concentrations of chloroform fraction of ethanol extract neem leaf; they were 5%, 10% and 20%. Repellent activity was carried out by counting number of mosquitoes alighted. The amount of repellent activity was obtained from the protection value which was then analyzed using two-ways Anova. The EC90 value gained from probit analysis at significance of 95%. Identification of chemical compound of chloroform fraction of ethanolic extract neem leaf was done using thin layer chromatography (TLC). The results showed that chloroform fraction of ethanolic extract neem leaf had repellent activity against Aedes aegypti mosquito. The average protection value for 6 hours in positive control group and chloroform fraction of ethanolic extract neem leaf at 5%, 10% and 20% concentration were 92,43%, 66,76%, 76,90% and 88,35%. The 6-hours treatment had caused decrease in protection value in all of treatment groups. The effective concentration of chloroform fraction ethanolic extract neem leaf to repel 90% population of Aedes aegypti mosquito for 6 hours treatment was 26,1%. The chemical compund of chloroform fraction of ethanolic extract neem leaf was terpenoid. Keyword: repellent, chloroform fraction of ethanolic extract neem leaf, Aedes aegypti